Are long-run price stability and short-run output stabilization all that monetary policy can aim for? - Giuseppe Fontana; Alfonso Palacio-Vera (Levy Economics Institute of Bard College, 2005)
A central tenet of the so-called new consensus view in macroeconomics is that there is no long-run trade-off between inflation and unemployment. The main policy implication of this principle is that all monetary policy can aim for is (modest) short-run output stabilization and long-run price stability-i.e., monetary policy is neutral with respect to output and employment in the long run. However, research on the different sources of path dependency in the economy suggests that persistent but nevertheless transitory changes in aggregate demand may have a permanent effect on output and employment. If this is the case, then, the way monetary policy is run does have long-run effects on real variables. This paper provides an overview of this research and explores how monetary policy should be implemented once these long-run effects are acknowledged.
Keywords: E5; E52; 330; monetary policy; new consensus; path dependency; opportunistic approach; Phillips-Kurve; Geldpolitik; Theorie